Price determination in monopolistic markets with inventory adjustment - M. Reza Rafati (Kiel Institute of World Economics (IfW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1981)
This paper presents a practical model for the analysis of the price determination mechanism in raw materials markets that are characterized by the dominance of a large firm. The model takes explicit note of the influence of inventory adjustments; it is postulated that the dominant firm's decision on price and production levels is negatively related to the difference between actual and desired inventory levels. In a first empirical test, the model is applied to an analysis of the nickel industry. The empirical results support the hypothesized role of inventories and show the importance of inventory adjustments relative to the other factors determining price and production behavior.
Keywords: 330